Sistem Keamanan Pintu Otomatis Berbasis IoT dengan Teknologi RFID dan Aplikasi Mobile Menggunakan Metode Fuzzy Mamdani - Haris Asysyauqi; Moh. Ferdi Andriansyah; Lya Nurul Ulla; Adi Sucipto (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
In the digital era, home security has become a crucial aspect with the increasing risk of theft due to the weaknesses of traditional lock systems. This study develops an automatic door security system based on the Internet of Things (IoT) by integrating Radio Frequency Identification (RFID) technology and mobile applications. This system allows users to lock and unlock the door and monitor the door condition and battery power in real-time from a distance. To increase flexibility and security, this system also utilizes the Mamdani Fuzzy logic method in decision making, based on parameters such as battery power, user distance from the door, and environmental security level. With this approach, the system can dynamically adjust access according to the situation. The test results show that the developed system is able to provide a more efficient, secure, and adaptive security solution compared to conventional locks, as well as providing better convenience and control for users in managing home security intelligently and integratedly.